Faktor yang Berpengaruh Terhadap Kinerja Usaha Di UMKM Kota Depok: (Jurnal Agribisnis Indonesia, 2024)
This study aims to examine and analyze the effect of business strategy and technology utilization on business performance with business sustainability an intervening variable in Depok City SMEs. This type of research is quantitative, using primary data obtained from distributing questionnaires directly. Data analyzed with Structural Equation Modeling (SEM) Lisrel. The data collection technique in this study is purposive sampling. The population in this study of SMEs entrepreneurs in Depok City. The number of samples taken was 110 respondents based on the calculation of the LVS model simplification technique Leave Variable Score The results of the study show that there is no direct effect either for business strategy, it does not have a significant effect on business performance and the use of technology does not have a significant effect on business performance. The indirect influence of these two variables is significant, namely that business strategy has a significant effect on business performance through business sustainability. The use of technology also has a significant effect on business performance through business sustainability, and business sustainability has been proven to have a significant effect on business performance. This research provides an overview of managerial implications in the form of recommendations and strategies for the sustainability of MSME businesses which will have an impact on improving the performance of MSMEs in Indonesia.